Community-based participatory interventions to improve food security: A systematic review - Doustmohammadian, Azam; Mohammadi-Nasrabadi, Fatemeh; Keshavarz-Mohammadi, Nastaran; Hajjar, Melika; Alibeyk, Sepideh; Hajigholam-Saryazdi, Maryam (Frontiers in Nutrition, 2022)
This systematic review aimed to evaluate community-based participatory (CBP) interventions to improve food security and/or its dimensions to highlight the scope and characteristics of interventions and extract the characteristics of effective interventions. The following electronic databases, including PubMed/MEDLINE, SCOPUS, EMBASE, Web of Science, and Google Scholar, were searched from 1980 to 30 August 2022 for relevant studies. We included randomized controlled trials (RCTs), cluster randomized controlled trials (cRCTs), controlled before and after studies (CBAs), non-randomized controlled trials (nRCT), and interrupted time series (ITS) studies to identify the community-based participatory interventions. Two reviewers independently evaluated the studies for eligibility, extracted data, and evaluated the risk of bias in the included studies using the Effective Public Health Practice Project (EPHPP). A descriptive analysis of the findings was performed. A total of twelve studies were included. The quality of all eligible studies (n=12) was rated as moderate/weak. Most CBP interventions were guided by formative research (n=9, 75%). Two main groups for utilized strategies were identified: agricultural and nutrition strategies. Agricultural strategies included agricultural education, preparing and improving soil and seeds, promoting and supporting gardening/harvesting utilizing traditional skills based on the local culture, and agroecological practices. Nutrition strategies included store and shopping programs, farmers’ markets, fresh fruit and vegetable programs, nutrition education programs for mothers, and food vouchers. The main outcomes improved in the CBP interventions were food security (n=2) and its dimensions, including availability (n=3), access (n=5), and utilization (n=2). All agroecological practices achieved statistically significant outcomes in the intended food security target(s). However, nutritional interventions were not effective for some access components such as mean adequacy ratio, fruit and vegetable intake, and nutrition environment of the stores. No studies evaluated stability outcome components of food security. CBP interventions guided by formative research data and agroecological practices were promising strategies to improve food security and its dimensions. Insufficient data on the stability components of food security and weak design studies were the considerable gaps in the research evidence reviewed. More research employing randomized experimental designs with adequate sample size and high retention rates is required.